Analisis Sistem Klaim BPJS Kesehatan pada Perkebunanan Socfindo Aek Pamienke - Siti Aminah Nasution (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The membership administration procedure factor, medical resume factor, diagnosis codeification factor and action codeification factor are still obstacles so that the claim file is returned by the BPJS Health verifier. The aim of this research is to find out the procedures for BPJS Health claims on socfindo plantations. Library research or literature study and quantitative approach. This research uses an online-based journal. As in the case of membership administration procedures, medical resume factors, diagnosis codification factors and action codification factors. The factor that caused the BPJS health claim files to be returned was the absence of a Standard Operating Procedure (SOP) governing patient registration regarding the collection of documents required for BPJS patient registration. Author authentication components and good record audits are not appropriate because there is no medical staff's signature and there are still blank sections. As well as writing non-specific diagnoses so that the codification is inaccurate and the coder relies on memorization not referring to ICD-10 or only looking at ICD-10 volume 3 without referring to volume 1. Keywords: BPJS, Claims, Literature, Procedures